The Impact of Streaming Services on the Traditional Cinemam - ALAKKASHA, IBRAHIM (İstanbul Kültür Üniversitesi, 2025)
This study utilizes a quantitative examination of shifting customer preferences, habits, and economic decision-making patterns to investigate how streaming services are transforming traditional cinema. By identifying the primary reasons of audience shifts apart from traditional cinema, the study analyses the disruptive impact of digital platforms such as Netflix, Disney+, and Amazon Prime on theatrical exhibition. A total of 200 respondents from various demographic segments participated in the survey, and the results were analysed using multiple regression models to examine reduced moviegoing, views on the survival of movie theaters, and willingness to pay for streaming services versus live experiences. The results show that 78% of respondents claimed they had been to the movies less frequently since using streaming services, and the most effective indicator of this loss was the variety of content (coefficient=0.237151, p=0.012092). Nonetheless, the social component of watching movies operates as a buffer, being positively associated with optimistic views on the sustainability of cinema in the future (coefficient=0.298967, p=7.2E-05). Market segmentation between content-focused viewers willing to pay for high-quality content and consumers with price preferences who refuse premium streaming payments was identified via economic research. According to the study's findings, traditional cinema could survive xby focusing on and improving its distinctive social and visual characteristics rather than engaging in accessibility or content diversity, even if streaming services have dramatically altered how individuals watch movies. These results provide industry stakeholders with recommendations for managing the evolving entertainment market and empirical evidence of streaming's diverse impact.
Keywords: Streaming Services; Traditional Cinema; Consumer Behavior; Digital Disruption; Film Exhibition; Regression Analysis